Una biblioteca in divenire. La biblioteca della Facoltà di Lettere dalla penna all'elaboratore - Tommaso, Urso (Firenze University Press, 2005)
This book illustrates the history of the Library of the Faculty of Arts and Philosophy of the University of Florence, tracing it from the origins up to the present: "from the pen to the computer", against the backdrop of Florence from unification to the threshold of the third millennium. The Library is inserted in the historic and geographical context in which it emerged, with references to the political and economic situation of Tuscany starting from the end of the Grand Duchy.